Genetic variation in folate metabolism is associated with the risk of conotruncal heart defects in a Chinese population - Xike Wang; Haitao Wei; Ying Tian; Yue Wu; Lei Luo (BMC, 2018)
Abstract Background Conotruncal heart defects (CTDs) are a subgroup of congenital heart defects that are considered to be the most common type of birth defect worldwide. Genetic disturbances in folate metabolism may increase the risk of CTDs. Methods We evaluated five single-nucleotide polymorphisms (SNPs) in genes related to folic acid metabolism: methylenetetrahydrofolate reductase (MTHFR C677T and A1298C), solute carrier family 19, member 1 (SLC19A1 G80A), methionine synthase (MTR A2576G), and methionine synthase reductase (MTRR A66G), as risk factors for CTDs including various types of malformation, in a total of 193 mothers with CTD-affected offspring and 234 healthy controls in a Chinese population. Results Logistic regression analyses revealed that subjects carrying the TT genotype of MTHFR C677T, the C allele of MTHFR A1298C, and the AA genotype of SLC19A1 G80A had significant 2.47-fold (TT vs. CC, OR [95% CI] = 2.47 [1.42-4.32], p = 0.009), 2.05-2.20-fold (AC vs. AA, 2.05 [1.28-3.21], p = 0.0023; CC vs AA, 2.20 [1.38-3.58], p = 0.0011), and 1.68-fold (AA vs. GG, 1.68 [1.02-2.70], p = 0.0371) increased risk of CTDs, respectively. Subjects carrying both variant genotypes of MTHFR A1298C and SLC19A1 G80A had a higher (3.23 [1.71-6.02], p = 0.0002) increased risk for CTDs. Moreover, the MTHFR C677T, MTHFR A1298C, and MTRR A66G polymorphisms were found to be significantly associated with the risk of certain subtypes of CTD. Conclusions Our data suggest that maternal folate-related SNPs might be associated with the risk of CTDs in offspring.